Does workfare work? India's employment guarantee during COVID-19 - Narayanan, Sudha; Oldiges, Christian; Saha, Shree (Wiley, 2022)
As many other countries, India leverages on a pre-existing workfare programme as a COVID-19 response. We combine monthly administrative data with migration and poverty statistics and provide four insights on the recent expansion of the programme. First, poorer districts include more households, that is, increasing extensive margin. Second, in districts with a high proportion of return migrants, there is no increase, and third, unmet demand for work is higher than the national average of 22.7%. Fourth, despite the expansion, the programme provided just 13.5 days per rural household. The programme requires attention to fulfil its promise as a credible safety net.